Ocena zarządzania personelem w urzędach administracji publicznej z wykorzystaniem metody CAF - Lisiecka, Krystyna; Papaj, Tomasz (Assessment of Human Resources Management in the Public Administration Offices by Using the CAF Method, 2008)
The paper is an attempt to evaluate the level of human resources management (HRM) in the offices of local public administration. The research included town/city halls in towns/cities of the poviat status from one of the largest Polish regions, i.e. Silesia Offices of urban poviats within the Śląskie Voivodeship have been selected primarily because they operate within one of the largest Polish agglomeration, providing services for approx. 2.7 million customers. The research was carried out in 2007 using the Common Assessment Framework (CAF) method. The level of HRM was described by the level of the implementation CAF criterion. To carry out the analysis, two criteria: "People" and "People Results" were chosen. The research verified the following research hypothesis: In the town/city halls in towns/cities of the urban poviat status from the Śląskie Voivodeship, the quality ofHR management is low. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 79-87